2020
DOI: 10.48550/arxiv.2006.01062
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rainbow Turán number of even cycles, repeated patterns and blow-ups of cycles

Abstract: The rainbow Turán number ex * (n, H) of a graph H is the maximum possible number of edges in a properly edge-coloured n-vertex graph with no rainbow subgraph isomorphic to H. We prove that for any integer k ≥ 2, ex * (n, C 2k ) = O(n 1+1/k ). This is tight and establishes a conjecture of Keevash, Mubayi, Sudakov and Verstraëte. We use the same method to prove several other conjectures in various topics. First, we prove that there exists a constant c such that any properly edge-coloured n-vertex graph with more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…We remark that our method is very different from the approach of O. Janzer [18], it is closer in spirit to that of [8].…”
Section: Rainbow Cycles and Subdivisionsmentioning
confidence: 79%
See 1 more Smart Citation
“…We remark that our method is very different from the approach of O. Janzer [18], it is closer in spirit to that of [8].…”
Section: Rainbow Cycles and Subdivisionsmentioning
confidence: 79%
“…Coloring an edge with color i if its end-vertices differ in coordinate i gives a proper coloring with no rainbow cycles. On the other hand, Das, Lee, and Sudakov [8] proved that average degree e (log n) 1/2+o(1) guarantees a rainbow cycle, which was further improved to O((log n) 4 ) by O. Janzer [18]. By studying properly edge colored α-maximal graphs with α ≈ 1/ log n, we are able to get within a log factor of the lower bound.…”
Section: Rainbow Cycles and Subdivisionsmentioning
confidence: 89%
“…) where ε k → ∞ as k → ∞. Very recently, Janzer [3] proved the conjecture by showing that ex * (n, C 2k ) = O(n 1+1/k ).…”
Section: Introductionmentioning
confidence: 92%
“…Theorem 1.2 (Janzer [3]). There is a constant C such that if n is sufficiently large and G is a properly edge-coloured n-vertex graph with at least Cn(log n) 4 edges, then G contains a rainbow cycle of even length.…”
Section: Introductionmentioning
confidence: 99%
“…Applying (4) gives a result which matches Theorem 2.3 due to our current knowledge of the extremal number of K + t . Among other impressive results, Janzer [12] showed that for fixed integers k, r ≥ 2,…”
Section: Relation To the Conlon-tyomkyn Problemmentioning
confidence: 99%